A new Bradyporus Charpentier, 1825 species from Iran (Orthoptera, Bradyporinae) - Garai-Gyulai, Adrienne; Ünal, Mustafa (Zootaxa, 2014)
The species of Bradyporus Charpentier, 1825 found in Turkey has been revised by the second author (M. Ünal, 2011). Bradyporus comprises thirteen species and subspecies at present. The species of the genus have a range of Central Palaearctic distribution; most of the species are Balkanian-Anatolian-Iranian, whereas some of them are restricted to Ukraine, the Caucasus, Transcaucasus, being inhabitants in the continental mountain steppe belt. It seems that Anatolia, with 8 species, and Balkans, with 6 species, are two diversity centres of this genus. Iran represented by only species, B. latipes (Stal, 1875). But, one more peculiar species is described from north west of Iran herein. The species of this genus are very similar to one another in their external features, however, detailed descriptions and characterizations are given for the authentic separation of the known species in the exhausting revision of the genus by the second author (Ünal, 2011).